2006
DOI: 10.1111/j.1525-1438.2006.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Stage III and IV ovarian cancer in the South West of England: five-year outcome analysis for cases treated in 1998

Abstract: This study evaluates the 5-year outcome data for the management of advanced ovarian cancer in the South West of England. Anonymized data for 361 stage III and IV ovarian cancers registered between January 1, 1998, and December 31, 1998, were obtained from the central gynecological tumor database. The following data were identified: age at diagnosis, FIGO stage, American Society of Anesthesiologists (ASA) grade, tumor differentiation, treating network and surgeon, amount of residual disease after debulking surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…In accordance with our study, publications in the literature also indicate the maximum residual tumor diameter as a prognostic factor and observed that survival increases as the residual tumor size decreases (12,13,22,23) . In our study, although the survival time in the group with a residual tumor diameter <1 cm was not statistically different, the fact that it is 11.3 months better than the group with no residual tumor could be explained by the small number of cases or with the discussion that cases with a residual tumor <1 cm could be considered as optimal as well.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In accordance with our study, publications in the literature also indicate the maximum residual tumor diameter as a prognostic factor and observed that survival increases as the residual tumor size decreases (12,13,22,23) . In our study, although the survival time in the group with a residual tumor diameter <1 cm was not statistically different, the fact that it is 11.3 months better than the group with no residual tumor could be explained by the small number of cases or with the discussion that cases with a residual tumor <1 cm could be considered as optimal as well.…”
Section: Discussionsupporting
confidence: 78%
“…operations were evaluated cases with a tumor diameter below 1 cm ranges from 33% to 67% (12,13) . The cases of our clinic are consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients diagnosed with OC, survival is theorized to be 100%, who are still alive after 5-years, are presumably living with the disease rather than living disease-free. 5 Our analysis demonstrated that the DFS was 18.3 months (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The Surveillance, Epidemiology and End Results-SEER database from 1995 to 2007 with epithelial OC who were actively followed-up and age 20 years or older were included for analyzing OS in the United States (40.692 patients) and OS was 65%, 44%, and 36% at 2, 5, and 10 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies found that higher grade remained significantly associated with survival. 6,9,11,17,18,20,23 A multivariate analysis showed that, for OC, the histological grade was a significant prognostic factor for DFS but not for OS. 19 As reported in several studies, grade as important prognostic factors is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Population based data on the number of advanced ovarian cancer patients operated by a gynaecological oncologist are available in the literature for Sweden [22], Finland [23], Switzerland [24], United Kingdom [25][26][27], Denmark [28], the Netherlands [29] and Norway [30]. Data are summarised in Table 1.…”
Section: Specialisation Of Surgeonsmentioning
confidence: 99%